Boxing Exercises as Therapy for Parkinson Disease. Issue 3 (July 2020) - Dawson, Rachael A.; Sayadi, Jamasb; Kapust, Lissa; Anderson, Lauren; Lee, Stacey; Latulippe, Al; Simon, David K.
Abstract : A noncontact boxing program called "Rock Steady Boxing" (RSB) is a popular exercise option for people with Parkinson disease (PD). This retrospective observational study assessed the impact of RSB on clinically relevant outcome measures in 62 PD patients. The change from program beginning to completion in the 30-second sit-to-stand (STS) test, the Timed Up and Go (TUG) test, a quality-of-life survey (the EQ-5D), and a satisfaction survey was analyzed. Significant improvement was observed in the STS and TUG tests for participants completing their first or second RSB sessions. These results indicate benefits of RSB for people with PD.